2010
DOI: 10.1155/2010/238573
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Determination of the Allergenic Potential of Egg White in Processed Meat

Abstract: Hen's egg white has been reported as a causative agent of allergic reactions, with ovalbumin, conalbumin, ovomucoid, and lysozyme being the major allergens. However, little is known about the effects of processing with heat and high pressure on the allergenicity of egg white proteins as ingredients in meat. For this purpose, the allergenic characteristics of such treated preparations were studied. The IgE-binding capacity was analyzed by EAST inhibition in raw and processed meat preparations using sera from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…High pressure treatment was found to cause the allergen reactivity of pasteurized liquid whole egg to decrease by 3.3 fold as detected by EAST inhibition. Combined thermal (heating to 70°C) and HHP at 600 MPa, 10 min caused a 8.9 fold reduction compared to control (70°C heating alone) that resulted in only 1.5 fold reduction in allergen reactivity (Hildebrandt et al, 2010). As demonstrated in the study, the combination of heat and HPP allowed for a greater reduction in overall food allergen reactivity.…”
Section: High Hydrostatic Pressuresupporting
confidence: 50%
“…High pressure treatment was found to cause the allergen reactivity of pasteurized liquid whole egg to decrease by 3.3 fold as detected by EAST inhibition. Combined thermal (heating to 70°C) and HHP at 600 MPa, 10 min caused a 8.9 fold reduction compared to control (70°C heating alone) that resulted in only 1.5 fold reduction in allergen reactivity (Hildebrandt et al, 2010). As demonstrated in the study, the combination of heat and HPP allowed for a greater reduction in overall food allergen reactivity.…”
Section: High Hydrostatic Pressuresupporting
confidence: 50%
“…Paradoxically, it has been shown that standard roasting of peanuts actually increases IgE binding to Ara h 1 and Ara h 2 [ 22 , 26 , 31 ]. However, fewer studies have looked at combinations of processing methods to alter the allergenicity of foods [ 23 , 29 , 30 , 32 ]. Because frying and boiling each had been shown to decrease the presence of highly allergenic peanut proteins in peanut extracts [ 20 , 27 , 33 ], and high heat [ 32 ] and high pressure [ 24 ] had been shown to decrease allergenicity of peanut allergens, we characterized the IgE binding capabilities of protein extracts from peanuts that were untreated (raw), or treated by a boiling and frying process (boiled/fried) and then subjected to various pressure/temperature/time treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Another study (Hu and others ) reported that low‐allergen brine shrimp could be obtained by treating the shrimp with papain in salt water under high pressure at 450 MPa. The allergenic potential of egg white proteins in meat significantly decreased when heat (70 °C) and HHP (600 MPa) were applied (Hildebrandt and others ). Additionally, the IgE binding of apple and celeriac allergen was effectively reduced with the combination of HHP and thermal processing (Meyer‐Pittroff and others ; Husband and others ).…”
Section: Resultsmentioning
confidence: 99%